2021
DOI: 10.1515/opag-2021-0225
|View full text |Cite
|
Sign up to set email alerts
|

Ideal pH for the adsorption of metal ions Cr6+, Ni2+, Pb2+ in aqueous solution with different adsorbent materials

Abstract: Industrialization increases the number of heavy metals released into the environment. Lead (Pb2+), nickel (Ni2+) and chromium (Cr6+) are among these toxic metals and cause irreversible effects on ecosystems and human health due to their bio-accumulative potential. The decontamination through adsorption processes using lignocellulosic wastes from agricultural and/or forestry processes is a viable solution. Hence, this work aimed at studying the effect of pH on the biosorption of the metal ions using four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Generally, due to its great influence on the surface charge of the adsorbent and the forms of the metal ions, the pH value is crucial to the adsorption behavior of metal ions, thus affecting the electrostatic interaction between the metal ions and the adsorbent . The ζ potential of MOFs gradually decreases with the increase of the pH value (Figure a), and the isoelectric point emerges at a pH value of 6.00, which indicates that the synthesized Cr-based MOF shows a positive charge when pH < 6.0.…”
Section: Resultsmentioning
confidence: 98%
“…Generally, due to its great influence on the surface charge of the adsorbent and the forms of the metal ions, the pH value is crucial to the adsorption behavior of metal ions, thus affecting the electrostatic interaction between the metal ions and the adsorbent . The ζ potential of MOFs gradually decreases with the increase of the pH value (Figure a), and the isoelectric point emerges at a pH value of 6.00, which indicates that the synthesized Cr-based MOF shows a positive charge when pH < 6.0.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, it can be suggested that metal biosorption occurs on the cell surface [ 41 ]. No aggregates of metal complex deposited in the form of granules on the cell surface were observed; thus, it can be concluded that sorption takes place through surface complexation, coordination, or ion exchange [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pH is one of the most important parameters in the monitoring of heavy metals, since it modifies the chemical form in which the metal is found in solution because of hydrolysis, precipitation, complexation, dissociation, and other reactions that occur between the medium and heavy metals, 28,29 while also affecting the surface chemistry of the electrode.…”
Section: Resultsmentioning
confidence: 99%